A study of thermal properties of sodium titanate nanotubes synthesized by microwave-assisted hydrothermal method. (November 2015) - Preda, Silviu; Rutar, Melita; Umek, Polona; Zaharescu, Maria
Graphical abstract: Highlights: The microwave-assisted hydrothermal route was used for titanate nanotubes synthesis. Conversion to single-phase nanotube morphology completes after 8 h reaction time. The nanotube morphology is stable up to 600 °C, as determined by in-situ XRD and SEM. Sodium ions migrate to the surface due to thermal motion and structure condensation. Abstract: Sodium titanate nanotubes (NaTiNTs) were synthesized by microwave-assisted hydrothermal treatment of commercial TiO2, at constant temperature (135 °C) and different irradiation times (15 min, 1, 4, 8 and 16 h). The products were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, differential scanning calorimetry and specific surface area measurements. The irradiation time turned out to be the key parameter for morphological control of the material. Nanotubes were observed already after 15 min of microwave irradiation. The analyses of the products irradiated for 8 and 16 h confirm the complete transformation of the starting TiO2 powder to NaTiNTs. The nanotubes are open ended with multi-wall structures, with the average outer diameter of 8 nm and specific surface area up to 210 m 2 /g. The morphology, surface area and crystal structure of the sodium titanate nanotubes synthesized by microwave-assisted hydrothermal method were similar to those obtained by conventional hydrothermal method.